CORPORATE GOVERNANCE DAN PENGARUHNYA TERHADAP INVESTASI RESEARCH & DEVELOPMENT (Studi Empiris Pada Perusahaan Industri Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021) - Khadafy Fadholi Syuhada; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2022)
This research was conducted to explore how much influence Corporate Governance has on Research & Development investments in pharmaceutical industry companies in Indonesia. Corporate Governance is measured by majority shareholders, independent commissioners, and institutional investors.The population in this study is a pharmaceutical industry company listed on the Indonesia Stock Exchange in the period 2016-2021. The samples obtained using the purposive sampling method amounted to 8 companies. The analytical technique used in testing this research hypothesis is a multiple linear regression analysis with SPSS software.The results of the study showed that the majority shareholder has a negative influence on Research & Development investment. Independent commissioners and institutional investors showed no influence on Research & Development investments.